Evening caffeine did not improve 100-m swimming time trials performed 60 min post-ingestion or the next morning after sleep - Newbury, J. W.; Saunders, B.; Gough, L. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
The potential ergogenic benefits of caffeine (CAF) are well known within the athletic community, often leading to its use in adolescent swimming cohorts to enhance their performance. However, it has previously been reported that CAF has sleep-disturbing effects, which could be detrimental to performance over consecutive days in multiday competitions. Moreover, the effects that evening CAF ingestion has on sleep, side effects, and next-day performances are yet to be researched in trained adolescents. In a double-blind, randomized, crossover design, eight national-level swimmers (age: 18 ± 1 years, height: 1.76 ± 0.06 cm, body mass [BM]: 69.4 ± 6.4 kg) ingested a capsule containing 3 mg/kg BM CAF or a placebo 60 min before an evening 100-m swimming time trial. The next morning, sleep was analyzed (Core Consensus Sleep Diary) and 100-m time trials were repeated. Side effects were analyzed via visual analog scales throughout the study. No differences were found for swimming performance (p = .911) in the evening (CAF: 59.5 ± 7.8 s, placebo: 59.9 ± 7.9 s, g = 0.06) or morning (CAF: 59.7 ± 7.7 s, placebo: 60.2 ± 7.9 s, g = 0.07). In addition, no group differences were found for any subjective side effects (e.g., anxiety: p = .468, tachycardia: p = .859, alertness: p = .959) or sleep parameters (e.g., sleep latency: p = .395, total sleep time: p = .574). These results question the use of a standardized 3 mg/kg BM CAF ingestion strategy for 100-m swimming time trials in trained adolescents, although objective measures may be needed to confirm that CAF does not affect sleep within this cohort.